A study of the Cu0.95Al0.05 alloy: stress-strain curve and microstructure - Medrano, Emilio (2018)
After fabricating five metallographic specimens of the Cu0.95Al0.05 alloy from electrolytic copper and aluminum, these ones were both microstructurally characterized by using a metallographic optical microscope at room temperature and subjected to mechanical traction in order to chart the stress-strain curve. From the characterization, it has been found out that the Cu0.95Al0.05 microstructure is composed of a single phase, and from the tensile tests, it has been obtained its rupture point, 249.361 MPa. The obtained results were explained in the framework of the theory of metals and metal alloys.